Zero budget-zero wastage natural farming:possible prototype to evergreen revolution in Agriculture - Halanaik, Bhavana (Indian Farming, 2022)
Zero Budget Farming can be achieved with the induction of Agave in the culturable waste, fallow and current fallow land which introduces accommodative and structural changes in farming. The potential to expand productionon vacant but suitable land with minimal inputs creates feasible economic systems, since cultivable land potential is shrinking in the country due to prolonged dry spells. Agave can be grown on large‐scale for production of biofuels and is likely to increase demand for labour and generate farm-based employment. It has the potential todrive the marginal and small farmers out of the vicious cycle of debt and suicide. It will generate regionalemployment, create common interest and social capital at every level, hence would play a great role in bringing evergreen revolution.